2019
DOI: 10.1177/0022034519847122
|View full text |Cite
|
Sign up to set email alerts
|

Salispheres from Different Major Salivary Glands for Glandular Regeneration

Abstract: Dysfunctional salivary glands (SGs) are a clinical challenge due to the lack of effective treatments. Cell therapy with stem/progenitor cells may improve this situation by providing promising therapeutic solutions. Therefore, exploring abundant cellular sources is important. Three major pairs of SGs are located in different anatomic regions: the parotid glands, the submandibular glands, and the sublingual glands. Although SG stem/progenitor cells can be isolated and cultivated from all major SGs as salispheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…After the successful generation of human SSp from the parotid gland (PG) and SMG using the same protocol applied to murine samples [25], researchers have tried to optimize culture conditions for long-term maintenance and functional maturation of SGOs. In general, floating culture and embedding into ECM material such as Matrigel are the most frequently utilized methods to generate SGOs and different culture conditions are required for SGSC expansion and induction of differentiation/ maturation (Table 1) [24][25][26][27][28][29][30][31][32]. Of note, Maimets et al [29] applied well-defined culture conditions for intestinal epithelial organoids to establish SGOs and revealed that the canonical Wnt/ β-catenin pathway is required for the maintenance of SGSC self-renewal in vitro.…”
Section: Sgos Derived From Sg Tissue Containing Aspcsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the successful generation of human SSp from the parotid gland (PG) and SMG using the same protocol applied to murine samples [25], researchers have tried to optimize culture conditions for long-term maintenance and functional maturation of SGOs. In general, floating culture and embedding into ECM material such as Matrigel are the most frequently utilized methods to generate SGOs and different culture conditions are required for SGSC expansion and induction of differentiation/ maturation (Table 1) [24][25][26][27][28][29][30][31][32]. Of note, Maimets et al [29] applied well-defined culture conditions for intestinal epithelial organoids to establish SGOs and revealed that the canonical Wnt/ β-catenin pathway is required for the maintenance of SGSC self-renewal in vitro.…”
Section: Sgos Derived From Sg Tissue Containing Aspcsmentioning
confidence: 99%
“…Similar to other exocrine organs, the production of saliva is tightly regulated by the autonomous nervous system via interactive crosstalk between receptor signaling [54][55][56]. In these aspects, Lee et al [32] successfully generated region-specific SGOs with unique cellular composition, although their secretory functions were not determined. Therefore, it would be important to check the expression pattern of receptors (cholinergic and purinergic receptors) and to test the reactivity of differentiated SGOs to various stimuli for functional evaluation.…”
Section: Conclusion and Limitations Of Current Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, clinical trials suggest stem cell therapy [ 16 , 17 , 19 ] combined with special cell culture methods such as spontaneous cell aggregation, hanging drop and rotating culture vessels [ 1 , 20 , 21 ] or scaffold material [ 22 25 ] to produce functional secretory epithelial organoids, and gene therapy [ 18 ] may offer new therapeutic options for radiation-induced xerostomia. Due to challenges related to keeping the functionality of SG cells, researchers have examined the potential benefit of using a combination of different biomaterials [ 26 , 27 ] and cell types to provide the optimal implant material for SG tissue engineering applications [ 28 30 ]. Nevertheless, fabricating a fully formed functional SG replacement in a controlled manner remains a challenge [ 11 ].…”
Section: Introductionmentioning
confidence: 99%